: Bahasa Inggris - Rohmansyah Rohmansyah; Muh Zuhri; Agung Danarto (IAIN Pekalongan, 2019)
Philanthropic hadiths are very interesting for contextual understanding in order to respond to social problems that occur in the community such as poverty and health problems which unwittingly increase day to day. This paper aimed to present philanthropic traditions about PKU Muhammadiyah hospital. The method used by researcher was analytical descriptive by using the method of socio-historical approach and Max Weber's social theory framework. The findings in this study were: First, philanthropic traditions of the hospital was delivered by the Prophet from the Companions of the Prophet around one hadith assisted by other hadiths. Second, contextualization of hadith understanding resulted in the formulation of its name; previously named Polyclinic. ​​Muhammad Sudja considered that Muhammadiyah has not had a hospital which handled needy people. Third, the roles of the PKU Muhammadiyah hospital are very large in the terms of public health services such as medical treatment, social services and in handling disasters. Fourth, the philanthropic movement conducted by the hospital are based on religious doctrines originating from Quran and al-Sunnah al-Maqbūlah so that it can realize the noble ideals of the Indonesians, namely the true Islamic community; the main, justice, safe and prosperous society, and hence blessed by Allah SWT.